Las normas de Seguridad e Higiene Industrial en la gestión de la Panadería “CRONST PAN” 2017 -2018 - Albán Quihuirí, Richard Vinicio (2019)
In this research topic, it will be demonstrated how the standards of industrial safety and hygiene affect the management of the Bakery Cronst Pan in the period 20 17-2018., in the development of products, for this reason, it is essential to apply the different Safety and Industrial Hygiene Standards, strictly observing the growth and stability of this company. According to the study conducted in the application of industrial safety standards, this is what causes loss of product, production risks, injuries, and incapacitating accidents; that harm the development of the company. It is essential to make continuous improvement of facilities and work environment, with this process, a guaranteed quality product is offered, as well as retaining trained, efficient, and responsible staff. Besides, the human element is the central aspect of the proper functioning of any company. Implement Industrial Safety Standards is essential since it is achieved to make correct signage in all areas of the company to avoid risks or accidents, maintenance of both facilities and machinery, the creation of an industrial safety committee and constant training to all staff as well. All of the above, with an adequate administration, will permit to increase the productivity in the company, and the results obtained will be optimal. If the company applies the company's Safety Standards, it avoids occupational accidents of different kinds, mentioned through the bibliographic review of laws and articles of the Constitution of the Republic, as well as books and virtual sources with connotations consistent and referring to the subject of security.